2021
DOI: 10.1007/s42761-021-00073-7
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 as Natural Intervention: Guilt and Perceived Historical Privilege Contributes to Structural Reform Under Conditions of Crisis

Abstract: The COVID-19 pandemic has been described as an unmasking of persistent racialized inequalities linked to South Africa’s oppressive past. However, such observations lack empirical support. Here we examined whether COVID-19 lockdown conditions encouraged greater perceptions of continuing structural racism together with motivational and behavioral support for social justice, and whether guilt or empathic concern undergirded such responses. A national sample of White South Africans’ data suggests that the pandemic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Perceived anti-White interpersonal and structural racism were less elevated than in Study 1, however. This latter finding might reflect the younger age of the present student sample, as age has also previously been associated with more progressive outcomes in the South African context ( Fourie and Verwoerd, 2022 ). Nevertheless, participants reported significantly greater perceptions of anti-White than anti-Black structural racism today, which suggests that competitive victimhood was also present in this younger sample.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Perceived anti-White interpersonal and structural racism were less elevated than in Study 1, however. This latter finding might reflect the younger age of the present student sample, as age has also previously been associated with more progressive outcomes in the South African context ( Fourie and Verwoerd, 2022 ). Nevertheless, participants reported significantly greater perceptions of anti-White than anti-Black structural racism today, which suggests that competitive victimhood was also present in this younger sample.…”
Section: Discussionmentioning
confidence: 54%
“…*** p < 0.001. Panel (A) is reprinted by permission from Springer Customer Service Centre GmbH: Springer Nature, Affective Science ( Fourie and Verwoerd, 2022 ). ns = not significant.…”
Section: Resultsmentioning
confidence: 99%
“…Considering that only 7% of the South African population between 25 and 34 years old has a tertiary education [ 102 ], university students are considered a super elite demographic that typically enjoys a more privileged lifestyle compared to most South Africans. Young and educated White South Africans have also been associated with more progressive racial perceptions and motivations [ 67 ], so that the racial empathy biases we observed might be more substantial in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Hughes and colleagues [ 65 ], for example, found that European American children expressed less racial bias after learning about historical racism experienced by African Americans. Indeed, various studies show that acknowledging the impact of historical suffering on continuing racialized inequality fosters support for social change and transformational redress [ 25 , 66 , 67 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 1994 with the demise of apartheid, colonial ideologies were rejected, and a democratically elected political party came into power that was representative of the Black majority. After almost three decades of liberation, however, racial polarization shows no signs of abating, the White minority continues to hold significant economic power and privilege, and wealth and income inequalities continue to be rampant within Black communities (Chatterjee, 2019; Fourie & Verwoerd, 2022; Hino et al, 2018; Sulla & Zikhali, 2018). This lack of structural change is particularly stark for the millions of people who continue to live in ever-expanding and dehumanizing township settlements (Wale et al, 2020).…”
Section: Dehumanization: a Brief Overviewmentioning
confidence: 99%